Analyzing visual attention during TAP learning and the effect of epistemic beliefs on the understanding of argument components. Issue 8 (24th May 2022) - Cheng, Chia-Hui; Yang, Fang-Ying
ABSTRACT: The purpose of this study was to analyze visual attention during students' learning of Toulmin's argument pattern (TAP) and the effects of epistemic beliefs in science on the understanding of argument components. A total of 43 undergraduates were recruited through the Internet. Online questionnaires targeting beliefs about knowledge in science [Conley, A. M., Pintrich, P. R., Vekiri, I., & Harrison, D. (2004). Changes in epistemological beliefs in elementary science students. Contemporary Educational Psychology, 29 (2), 186–204] and beliefs about justification for knowing in science [Ferguson, L. E., & Bråten, I. (2013). Student profiles of knowledge and epistemic beliefs: Changes and relations to multiple-text comprehension. Learning and Instruction, 25, 49–61] were used to assess students' epistemic beliefs. Identification tests for the understanding of TAP were performed before and after an argument reading treatment designed as a self-learning activity. The whole reading process was recorded by the eye-tracking system. To explore the effect of the reading treatment, participants were divided into a progress (P) group and a no-progress (NP) group based on their learning gains.The results indicated that students' epistemic beliefs in science and their learning strategies would affect their TAP learning performance. The analyses of visual attention distribution indicated that integration information indicated by inter-scanning counts would enhance students' learning performance. In addition, the LSA results suggested that understanding of data is of primary importance when learning TAP. Suggestions on how to guide students in learning TAP are provided based on the findings.